Oral Health in Relation to Nutrition a Literature Review - Ramal Ahmed Zangana, (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: This review deals with complex relationship among diet, nutrition and their implications on oral health and this review also reveals the oral diseases are associated with considerable pain, anxiety and impaired social functioning. Search method: An electronic search was done in the google website, PubMed, and google scholar. Articles from 1993 to 2017 were included in the review. Summery and Conclusions: Mouth being a reflecting mirror of general health often helps in early diagnosis of many diseases and disturbances. Like any other system of our body, In this way nutrition and oral health are mutually dependent and hence an extensive understanding of this inter relationship is essential for healthy life the customary allowance of food and drink taken by any person per day varies from nutrition, which involves the metabolic processes and utilization of nutrients in the food. Malnutrition affects the oral health and a poor oral health in turn, may lead to malnutrition. Malnutrition may alter the homeostasis, which can lead to disease progression of the oral cavity, reduce the resistance to the microbial biofilm and reduce the capacity of tissue healing. A poor diet was significantly associated with increased odds of oral disease. Dietary advice for the prevention of oral diseases has to be a part of routine patient education practices. Inconsistencies in dietary advice may be linked to inadequate training of professionals. Literature suggests that the nutrition training of dentists and oral health training of dietitians and nutritionists is limited.